175 years of financial risks and returns in central banking - Kim Abildgren (Danmarks Nationalbank, 2016)
Central banks around the world have substantial domestic and foreign financial assets and liabilities on their balance sheets reflecting their role as monetary authorities. This paper explores the long-term trends in risk and return in central banking using the central bank of Denmark, Danmarks Nationalbank, as a case study. The paper presents new annual time series data on Danmarks Nationalbank's balance sheets and profit from financial items 1839-2014 and analyses developments in core earnings and earnings from assuming additional risks within a simple asset/liability framework. During the past 175 years or so core earnings associated with the basic functions and the risks that unavoidable follow from being a central bank have on average accounted for the main part of the Nationalbank's financial return. There has, however, been a downward trend in core earnings since the early 1980s in step with the general decline in the interest-rate level. During this period earnings from additional risks taken as a financial institution by evaluating the expected risk-return trade-off have contributed significantly to the financial return. The paper adds to the literature by taking a long-term historical perspective that makes it possible to trace potential links between the macro economic environment, the monetary-policy strategy and financial risks and returns in central banking. – – Centralbankerne rundt omkring i verden har betydelige indenlandske og udenlandske finansielle aktiver og passiver på deres balance, hvilket afspejler deres rolle som pengepolitiske myndigheder. Dette papir belyser de langsigtede tendenser i risiko og afkast ved centralbank-virksomhed med Danmarks Nationalbank som eksempel. Papiret præsenterer nye årlige tidsrækkedata for Nationalbankens balance og finansielle resultat 1839-2014 og analyserer udviklingen i basisindtjeningen og indtjeningen fra yderligere risikotagning inden for en simpel aktiv/passiv ramme. Gennem de seneste godt 175 år har basisindtjeningen forbundet med de funktioner og risici, som uundgåeligt følger af at være centralbank, gennemsnitligt set tegnet sig for hovedparten af Nationalbankens finansielle resultat. Siden begyndelsen af 1980'erne har der dog været en nedadgående tendens i basisindtjeningen i takt med det generelle fald i renteniveauet. I denne periode har indtjeningen fra yderligere risiko taget som en finansiel virksomhed ud fra en afvejning af forventet afkast versus risiko bidraget væsentligt til det finansielle resultat. Papiret bidrager til litteraturen med et langsigtet historisk perspektiv, som gør det muligt at belyse det potentielle samspil mellem de makroøkonomiske vilkår, den pengepolitiske strategi og finansielle risici og af kast ved centralbankvirksomhed.
Keywords: E42; E51; E52; E58; F33; G11; N23; N24; 330; Central banking; Risk management; Accounting; FX reserves; Monetary history